Strategies to Build Relationships with the Media - Rani, Fitri Muha; Silvira, Melva (Semantik: Journal of Social, Media, Communication, and Journalism, 2023)
Building relationships with the media is very important for public relations practitioners. Their success in carrying out PR tasks in order to reach the attention of audiences is largely determined by their understanding of strategies for building relations with the media as well as the intelligence and tactics of public relations practitioners in building relationships with media. Good relations with the mass media are built using the right communication strategy, namely the method used for smooth communication between public relations and the mass media. The good relations referred to here are good relations with media institutions and between public relations and journalists. A good relationship with the mass media is very important for public relations. Like an army going out to battle, he needs understanding and mastery of war strategy. Likewise with public relations practitioners, for the success of publicity, also requires understanding and mastery of strategies to build relationships with the media